Non‐invasive assessment of temporal changes in myocardial microvascular function in persons with type 2 diabetes and healthy controls. Issue 6 (25th January 2021) - Rasmussen, Ida K. B.; Hasbak, Philip; von Scholten, Bernt J.; Laursen, Jens C.; Zobel, Emilie H.; Jorge Diaz, Lars; Holmvang, Lene; Ripa, Rasmus S.; Rossing, Peter; Kjaer, Andreas; Hansen, Tine W.
Abstract: Background: Cardiac Rubidium‐82 ( 82 Rb) positron emission tomography/computed tomography (PET/CT) provides a measure of the myocardial blood flow and the myocardial flow reserve, which reflects the function of both large epicardial arteries and the myocardial microcirculation. Knowledge on changes in the myocardial microvascular function over time is lacking. Methods: In this cohort study, we recruited 60 persons with type 2 diabetes and 30 non‐diabetic controls, in 2013; all free of overt cardiovascular disease. All underwent a cardiac 82 Rb PET/CT scan. In 2019, all survivors (n = 82) were invited for a repeated cardiac 82 Rb PET/CT scan using the same protocol, and 29 with type 2 diabetes and 19 controls participated. Results: Median duration between visits was 6.2 years (IQR: 6.1–6.3). In the total cohort, the mean age was 66.4 years (SD: 9.3) and 33% were females. The myocardial flow reserve was lower in persons with type 2 diabetes compared to controls ( p  = 0.002) but there was no temporal change in the myocardial flow reserve in participants with type 2 diabetes: mean change: −0.22 (95% CI: −0.47 to 0.02) nor in controls: −0.12 (−0.49 to 0.25) or when comparing type 2 diabetes to controls: mean difference: −0.10 (95% CI: −0.52 to 0.31). The temporal reduction in stress‐induced myocardial blood flow did not differ within the groups but was more pronounced in type 2 diabetes compared to controls: mean difference: −0.30 (95% CI: −0.55 to −0.04). Conclusion: The myocardial microvascular function was impaired in persons with type 2 diabetes compared to controls but did not change significantly in either of the groups when evaluated over 6 years.